IMPLEMENTATION OF THE DEMONSTRATION METHOD TO IMPROVE TEACHERS’ ABILITY IN UTILIZING THE ENVIRONMENT AS A LEARNING RESOURCE AT SANTO TARCISIUS KINDERGARTEN DUMAI - Aida (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper is based on teachers’ low ability to utilize the environment as a learning source at TK Santo Tarcisius Dumai. It can be seen from the symptoms that many kindergarten teachers still have not implemented yet the concept of environmental insight implementation, a few kindergarten teachers still have empowered the environment as a source of learning, and some educational institutions, especially kindergartens, still do not apply the school concept of environmental insight. The research subjects involved teachers who teach in kindergarten. The type of research is School Action Research (PTS), which aims to determine the success of increasing teachers' abilities in utilizing the environment as a learning source in teaching through demonstration methods at Kindergarten of Santo Tarcisius Dumai. Based on the results of the analysis and discussion in cycle I and cycle II mentioned above, it can be concluded that the application of the demonstration method can improve the teacher's ability to utilize the environment as a learning resource at Santo Tarcisius Kindergarten Dumai. In the first cycle, the teacher's ability to utilize the environment as a learning resource obtained a classical value of 67% and increased to 85% in cycle II.